The intravenous use of commercial disinfectants in the treatment of Novel Coronavirus (COVID-19): Unconventional, but is there evidence against it? - Shah, Adarsh; Leung, Edmund (Asian Journal of Medical Sciences, 2020)
Background: On 24th April 2020, United States President Donald J. Trump suggested the use of commercial surface disinfectants to treat patients infected with COVID-19. In his speech, President Trump also proposed medical research be conducted. However, there are controversies regarding the toxicity of the disinfectant’s main ingredients sodium hypochlorite. Aims and Objective: The purpose of this international collaborative study is to assess on feasibility and safety of disinfectants in human use. Materials and Methods: Several safety labels of common commercialised brands of surface disinfectant from United Kingdom and New Zealand. Furthermore, literature search was conducted through Pubmed on keywords keywords “sodium hypochlorite” AND “poisoning” AND “intravenous drug user”. Result: All safety labels advised hazardous warning regarding irritation and caustic burns if ingested. They all suggest water to wash out the effect if exposed to any mucus membrane such as eyes and broken skin. No safety information was given by any of the brands against subcutaneous or intravenous injection. No death in human was reported resulting from oral ingestion. There were 2 case reports: one of blindness and one of fibrosing alveolitis resulting from ingestion during a domestic dispute. Intravenous injection has only been seen in attempted murder cases or by intravenous drug users. All the reported cases have resulted in 2 deaths, organ failures and venous thrombosis including pulmonary embolism. Conclusion: There is no safety warning from the manufacturers of the studied surface disinfectants regarding intravenous use. Intravenous injections in the literature suggests significant toxic outcome including death. Randomised controlled trials on animals may be required to assess the risk of intravenous injection of surface disinfectants against the risk of death from COVID-19 infection.